ANALISIS PENGGUNAAN FAKTOR-FAKTOR PRODUKSI PADA USAHATANI JANGGELAN DI KECAMATAN KARANGTENGAH KABUPATEN WONOGIRI - Jesica Theresia; Erlyna Wida Riptanti; Susi Wuri Ani (Caraka Tani: Journal of Sustainable Agriculture, 2016)
This research was aimed to analyze the amount of the costs, the revenue and the income of black grass jelly farming, and analyze the use of factors which influence the production of black grass jelly in Karangtengah Sub-District, Wonogiri District. The location of the research was determined by purposive sampling method. The Village that used on this research was selected bypurposive sampling method. The samples in this research were 40 respondents selected by using proportional random sampling method. The data used in this research was primary and secondary data. The data analysis that usedon this research were:(1) the analysis of the costs, the reception and the income of the farming, (2) the analysis of production function by Cobb-Douglas.The reseach result, based on the analysis of the black grass jelly farming with the land area of 0,37 Ha explained the cost of establishing the farming was Rp 4.425.482,50/PT , the reception of the farming was Rp19.930.000,00/PT and the  income of the farming was Rp 15.504.517,50/PT. The equation function by Cobb-Douglas was : Ln = 7,224 + 0,767 ln X1 – 0,162 ln X2 + 0,107 ln X3 + 0,001 ln X4+ 0,317 ln X5 + 0,007 ln X6. The result of regression showed that production factors such as; land area, the number of seeds, urea fertilizer, phonska fertilizer, manure, and the labors had the real impact toward the production of black grass jelly.Individually, the production factors such as; urea fertilizer, phonska fertilizer, and the labors did not have the real impact on production of black grass jelly.